Deaths and Hospitalizations for Falls in the Brazilian Elderly: Integrative Literature Review - Barros, Iarema Fabieli Oliveira de (2016)
Falls have become a significant part of public health problems and occupy a prominent position in health statistics in most countries, including Brazil. This study is an integrative review of the literature whose methodology seeks the systematized research on the problem of falls, with the purpose of identifying possible knowledge gaps. It was verified that the female sex represents a greater proportion of hospitalizations and attendances in emergency and emergency services, whereas in males the fall usually has as main outcome the death. The dimensions of occurrences involving elderly people who suffer falls are multiple and reinforce the need for studies to support the formulation of public policies to prevent this disease.